Contemporary epidemiological overview of malaria in Madagascar: operational utility of reported routine case data for malaria control planning. (December 2016) - Howes, Rosalind; Mioramalala, Sedera; Ramiranirina, Brune; Franchard, Thierry; Rakotorahalahy, Andry; Bisanzio, Donal; Gething, Peter; Zimmerman, Peter; Ratsimbasoa, Arsène
Abstract Background Malaria remains a major public health problem in Madagascar. Widespread scale-up of intervention coverage has led to substantial reductions in case numbers since 2000. However, political instability since 2009 has disrupted these efforts, and a resurgence of malaria has since followed. This paper re-visits the sub-national stratification of malaria transmission across Madagascar to propose a contemporary update, and evaluates the reported routine case data reported at this sub-national scale. Methods Two independent malariometrics were evaluated to re-examine the status of malaria across Madagascar. First, modelled maps ofPlasmodium falciparum infection prevalence (Pf PR) from the Malaria Atlas Project were used to update the sub-national stratification into 'ecozones' based on transmission intensity. Second, routine reports of case data from health facilities were synthesized from 2010 to 2015 to compare the sub-national epidemiology across the updated ecozones over time. Proxy indicators of data completeness are investigated. Results The epidemiology of malaria is highly diverse across the island's ecological regions, with eight contiguous ecozones emerging from the transmission intensityPf PR map. East and west coastal areas have highest transmission year-round, contrasting with the central highlands and desert south where trends appear more closely associated with epidemic outbreak events. Ecozones have shown steady increases in reported malaria cases since 2010, with a near doubling of raw reported case numbers from 2014 to 2015. Gauges of data completeness suggest that interpretation of raw reported case numbers will underestimate true caseload as only approximately 60–75 % of health facility data are reported to the central level each month. Discussion A sub-national perspective is essential when monitoring the epidemiology of malaria in Madagascar and assessing local control needs. A robust assessment of the status of malaria at a time when intervention coverage efforts are being scaled up provides a platform from which to guide intervention preparedness and assess change in future periods of transmission.